2019
DOI: 10.1055/a-0835-6447
|View full text |Cite
|
Sign up to set email alerts
|

Consider Role of Glutamatergic Habenula-projecting Globus Pallidus in OCD

Abstract: Recently, in a review article in this journal, Vlček and colleagues described the putative role played by the glutamatergic system in obsessive-compulsive disorder (OCD) and how this might explain the effects of certain treatments. They describe a neuroanatomical model, which includes a specific role of the amygdala-hippocampus complex (AHC) and would complete the classic cortico-striatal-thalamo-cortical (CSTC) mechanism of OCD. The role of the AHC can perhaps be better understood when considering its ancien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For example, DBS of LHb in rats reduced sucrose seeking and cocaine seeking behavior (51, 52) consistent with the putative role of Hb in addiction (17,34,53,54). Furthermore, studies have demonstrated that the Hb plays a role in the pathophysiology of a number of neuropsychiatric disorders beyond depression and addiction such as schizophrenia (15,55,56), bipolar disorder (BD) (15,33,(57)(58)(59), obsessive-compulsive disorder (OCD) (60,61) and autism (62).…”
Section: Introductionmentioning
confidence: 75%
“…For example, DBS of LHb in rats reduced sucrose seeking and cocaine seeking behavior (51, 52) consistent with the putative role of Hb in addiction (17,34,53,54). Furthermore, studies have demonstrated that the Hb plays a role in the pathophysiology of a number of neuropsychiatric disorders beyond depression and addiction such as schizophrenia (15,55,56), bipolar disorder (BD) (15,33,(57)(58)(59), obsessive-compulsive disorder (OCD) (60,61) and autism (62).…”
Section: Introductionmentioning
confidence: 75%
“…However, the distinct connections of the (more than 15) different habenula subnuclei are organised in far too complex a way to allow fruitful analysis of the underlying mechanisms to explain these findings. In addition, major depressive disorder (Loonen & Ivanova, 2016b;Duman et al, 2019), obsessive-compulsive disorder (Vlček et al, 2018;Loonen & Ivanova, 2019b) and schizophrenia (Owen et al, 2016;Guan et al, 2021) are composite disorders which are likely to be simultaneously caused by multiple neurobiological disturbances to a mutually variable extent. The role of the habenula in the symptoms of neuropsychiatric disorders based on non-congenital brain damage has been little investigated.…”
Section: Putative Involvement Of Habenular Physiology In (Neuro) Psyc...mentioning
confidence: 99%
“…It is, furthermore, a key region for reward processing and critically involved in a number of depressive behaviours 1 , 6 , 31 , 32 . In addition, studies have implicated the habenula in bipolar disorder (BD) 33 35 , obsessive–compulsive disorder (OCD) 36 , 37 as well as schizophrenia 38 , 39 and altered habenula volume has been reported in subjects diagnosed with BD and schizophrenia 40 , 41 . Previous studies have reported altered amygdala volume in subjects with ASD compared to age matched controls 25 , 42 .…”
Section: Introductionmentioning
confidence: 99%